2012
DOI: 10.3389/fncel.2012.00031
|View full text |Cite
|
Sign up to set email alerts
|

Do genes and environment meet to regulate cerebrospinal fluid dynamics? Relevance for schizophrenia

Abstract: Schizophrenia is a neurodevelopment disorder in which the interplay of genes and environment contributes to disease onset and establishment. The most consistent pathological feature in schizophrenic patients is an enlargement of the brain ventricles. Yet, so far, no study has related this finding with dysfunction of the choroid plexus (CP), the epithelial cell monolayer located within the brain ventricles that is responsible for the production of most of the cerebrospinal fluid (CSF). Enlarged brain ventricles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 86 publications
(110 reference statements)
0
21
0
1
Order By: Relevance
“…The most consistent pathological feature of schizophrenia is enlargement of the brain ventricles, which is present at the time of disease onset (Palha et al, 2012;Steen et al, 2006). This enlargement could be linked to dysfunction of CSF secretion at the CP because AQP1 and AQP4 are abundantly expressed at the CP, and AQP1 is located within the genetic loci that are strongly implicated in schizophrenia (Palha et al, 2012;Brown et al, 2004). Furthermore, it has been shown that the incidence of CP calcifications (CPC) before the age of 25 years is relatively high in schizophrenic patients (40%) compared to controls (20%) (Bersani et al, 1999).…”
Section: Schizophreniamentioning
confidence: 97%
See 3 more Smart Citations
“…The most consistent pathological feature of schizophrenia is enlargement of the brain ventricles, which is present at the time of disease onset (Palha et al, 2012;Steen et al, 2006). This enlargement could be linked to dysfunction of CSF secretion at the CP because AQP1 and AQP4 are abundantly expressed at the CP, and AQP1 is located within the genetic loci that are strongly implicated in schizophrenia (Palha et al, 2012;Brown et al, 2004). Furthermore, it has been shown that the incidence of CP calcifications (CPC) before the age of 25 years is relatively high in schizophrenic patients (40%) compared to controls (20%) (Bersani et al, 1999).…”
Section: Schizophreniamentioning
confidence: 97%
“…Not every schizophrenic individual responds to therapy and since drugs improving negative symptoms are lacking, there is a need for new therapeutic, and maybe preventive, approaches (Arroll et al, 2014). The most consistent pathological feature of schizophrenia is enlargement of the brain ventricles, which is present at the time of disease onset (Palha et al, 2012;Steen et al, 2006). This enlargement could be linked to dysfunction of CSF secretion at the CP because AQP1 and AQP4 are abundantly expressed at the CP, and AQP1 is located within the genetic loci that are strongly implicated in schizophrenia (Palha et al, 2012;Brown et al, 2004).…”
Section: Schizophreniamentioning
confidence: 97%
See 2 more Smart Citations
“…CP is highly vulnerable to damage on head injuries, infections, and ischemic conditions (Maxwell et al 1992). Furthermore, Palha et al (2012) mentioned acute peripheral inflammation in CP.…”
Section: Introductionmentioning
confidence: 99%